2012
DOI: 10.1177/1553350611432720
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Type II Endoleak by Laparoscopic Inferior Mesenteric Artery Ligation

Abstract: Abdominal aortic aneurysm repair by endovascular techniques have gained wide acceptance as a treatment option. A potential well-known complication of endovascular repair includes endoleak. Specifically, type II endoleak, which is described as retrograde flow into the aneurysm sac through collateral vessels, can occur in up to 30% of patients. Certain preoperative factors can predict which patients may develop type II endoleak. This article describes laparoscopic inferior mesenteric artery ligation prior to end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recently, on the basis of different experience, there has been a trend toward preventing EIIs instead of treating their complications after they develop. Brenes et al 12 reported laparoscopic IMA ligation before EVAR; Muthu et al 13 have described routine intraoperative selective IMA embolization and thrombin injection into the aneurysm sac just before EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, on the basis of different experience, there has been a trend toward preventing EIIs instead of treating their complications after they develop. Brenes et al 12 reported laparoscopic IMA ligation before EVAR; Muthu et al 13 have described routine intraoperative selective IMA embolization and thrombin injection into the aneurysm sac just before EVAR.…”
Section: Discussionmentioning
confidence: 99%